Comparison of Structural Performance of Fixbase and Base Isolation in KAI Boutique Hotel Building with Response Spectrum - Angga Grecia; Istiqomah Istiqomah; Nanang Dalil Herman (Portal: Jurnal Teknik Sipil, 2025)
This study compares the seismic performance of fixed-base and base-isolated structures for the KAI Boutique Hotel Building in Bandung, a region prone to earthquakes due to active faults such as the Lembang, and Baribis Faults. This study aims to analyze the differences in base shear, displacement, and inter-story drift between the two structural systems using response spectrum analysis, and evaluate the seismic performance level based on ATC-40 guidelines. The research methodology involved modeling an 11-story hotel building in ETABS v.18.1.0 with two scenarios: fixed-base and base- isolated models analyzed by response spectra. The base isolation system uses High Damping Rubber Bearings (HDRB). The main parameters analyzed include base shear, and inter-story deviation. The results show that base isolation significantly reduces base shear. For example, by response spectrum analysis, the base shear is reduced by 54.5% in the X direction and 56.3% in the Y direction compared to the fixed-base system. Base isolation effectively reduced the average inter-storey deviation by 68% in the X direction and 73% in the Y direction. Based on ATC-40, both fixed-base and base-isolated structures achieved the "Immediate Occupancy (IO)" performance level in all analyses, showing minimal structural and non-structural damage, allowing the building to continue functioning after the earthquake